Variables associated with stability after Le Fort I osteotomy for skeletal class III malocclusion. Issue 9 (September 2021) - Lee, C.C.; Xhori, O.; Tannyhill, R.J.; Kaban, L.B.; Peacock, Z.S.
Abstract: The purpose of this study was to assess skeletal stability and predictors of relapse in patients undergoing an isolated Le Fort I osteotomy. A retrospective cohort study of 92 subjects undergoing Le Fort I osteotomy for Class III malocclusion was implemented. Predictor variables were demographic and perioperative factors. The primary outcome variable was postoperative skeletal position with relapse defined as >2 mm sagittal and/or vertical change at A-point on serial lateral cephalograms at immediate postoperative, 1 year, and latest follow-up time points. Mean advancement at A-point was 6.28 ± 2.63 mm and mean lengthening was 0.92 ± 1.76 mm. Eight subjects (8.70%) had relapse (>2 mm) in the sagittal plane, and two subjects (2.17%) in the vertical plane. No subjects required reoperation for relapse as overbite and overjet remained in an acceptable range due to dental compensation. In regression analysis, magnitude of maxillary advancement was an independent predictor of relapse in the sagittal plane ( P  = 0.008). There were no significant predictors of relapse in the vertical plane. This study suggests that isolated Le Fort I osteotomy for correction of skeletal Class III malocclusion is a stable procedure and that greater advancement is an independent risk factor for sagittal relapse.